Pembuatan Konten di Reels Instagram Sebagai Media Iklan pada Aura Park Malang - Chandra Arga Saputra; Fatkhur Rochman; Maskur (INDO PUBLISHING, 2025)
This study aimed to make content on the Instagram reels feature as an advertising medium to promote Aura Park Malang housing using the Adobe Premier Pro Application. The study used the Action Research method consisting of planning, action, observation, and reflection. The assessment of content effectiveness was carried out through the Grammar of Edit approach for the quality of video marketing content, as well as the EPIC Model (Empathy, Persuasion, Impact, Communication) to measure the effectiveness of video marketing content. The sample in this study consisted of 11 respondents, including owners, employees, marketing experts, computer experts, and prospective consumers. The results of the questionnaire analysis on Grammar of Edit showed a score of 85%, this is categorized as feasible and meets the standards in video quality. While the results of the analysis on the EPIC rate were 4.4 on video 1, 4.4 on video 2, 4.3 on video 3, 4.3 on video 4 and 4.2 on video 5. There was an increase in the effectiveness score on video 5 after revisions were made in the second cycle by obtaining an average EPIC score of 4.3. Therefore, all video content are included in the